(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
Virtual education has experienced global growth, but in rural communities in Colombia, limited internet ac- cess and lack of technological resources are significant challenges. This qualitative study explores these obstacles and their impact in depth. The methodology involves documentary analysis, review of reliable sources and categorization of results. Preliminary findings highlight the lack of access to technological re- sources and connectivity as key barriers, along with the lack of training for teachers and students. This underscores the need to address the digital divide and provide adequate support in rural Colombian educa- tion. Preliminary findings highlight limited internet access, limited technological resources and lack of train- ing as key barriers. Overcoming these obstacles will not only promote equal educational opportunities in these areas, but will also contribute to the sustainable development of rural communities and strengthen the resilience of the education system in the face of crises such as the COVID-19 pandemic.